(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Drapeability is one of the most important visual properties affecting garment appearance. Even though there are many studies concerned with fabric drape, understanding about the drape behaviour of garments is very limited. This study analyzes the key properties affecting the drape behaviour of garments to provide prediction equations. Results are statistically analyzed. From multiple regression analysis, drape rank scores obtained from subjective analyses are predicted using weight, bending modulus and extensibility measured at 100 gf/cm with a correlation coefficient of 0.94. Ranking values obtained from subjective analyses can be more easily predicted using both circularity and wave length minimum. A new equation was derived to predict drape rank score values of garments (correlation coefficient r = 0:97) depending on circularity and wavelength minimum.